Ownership Concentration and Firm Performance in Transition Economies: Evidence from Montenegro - Zorica Kalezić (Journal of Central Banking Theory and Practice, 2015)
The relationship between ownership concentration and firm performance has been the focal point of corporate governance literature and the subject of rather rich empirical literature. However, the current literature lacks uniformity and consensus regarding the nature and direction of this relationship. This research aims to contribute to this literature by investigating the relationship in a small and open transition economy of Montenegro. We use primary data from the period 2004-2008 to analyse, for the first time, the impact of ownership concentration on firm performance in Montenegro. The results support the hypothesis that high ownership concentration enables effective monitoring by investors to protect their interests; i.e. in the specific circumstances of transition, ownership structure may be (temporarily) used as a viable substitute for the still underdeveloped corporate governance framework.
Keywords: G32; G34; 330; ownership structure; concentration; firm performance; corporate governance; Transition Economies; Montenegro